PERDAGANGAN INTERNASIONAL VAKSIN DALAM PERTUMBUHAN EKONOMI NEGARA - Redjeki, Finny (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
As for the objectives in research on the economy of a country, economic growth is the most prominent context because it can be a benchmark for the nation's economic achievements, and this economic growth is one of the indicators of development progress because the driver of growth is international trade. As in international trade which is growing large due to cooperation carried out by various countries. This research method uses a qualitative descriptive research method, namely an overview of the target. The point is that the author wants to explain how the role of international trade in economic growth. International trade is trade carried out by residents of one country with residents of another country on the basis of mutual agreement. International trade carried out with export-import activities has a very important role and impact on economic growth. International trade opens up new market areas that are wider in domestic revenue sharing. A country that carries out import-export activities has comparative, competitive, and independent advantages in managing natural resources, and progress on industrialization and labor.